Pelatihan Orang Tua sebagai Mitra Pendidikan untuk Meningkatkan Prestasi Belajar di SMA Lhoksemawe - Ayunda, Desy Sary; Muhammad; Nuraina; Wulanda (PASAI : Jurnal Pengabdian kepada Masyarakat, 2023)
parent training as an education partner, aims to empower parents with the right knowledge, skills, and strategies to support their children's learning process at home. This training will cover various aspects, from understanding the physical and psychological development of students in their teens, to techniques for dealing with different learning challenges. By actively involving parents, we hope to create a positive synergy between home and school. This method involved in-depth interviews with parents, students, and the school to understand their views on the training and the changes that occurred in educational support following the training. The research results show that parent training as an educational partner can have a positive impact on the level of student achievement in secondary schools. Effective parental training can increase their involvement in children's education, motivate students to study harder, and increase participation in school activities. In addition, parents who are trained have a better ability to provide support and assistance to overcome learning difficulties. active involvement of parents in supervising and controlling student learning activities has a positive impact on academic achievement. Parents who are directly involved in supervising students' homework and schoolwork help create a more structured and supportive learning environment.